Cover Crop Biomass Production in Temperate Agroecozones. (1st July 2019) - Ruis, Sabrina J.; Blanco‐Canqui, Humberto; Creech, Cody F.; Koehler‐Cole, Katja; Elmore, Roger W.; Francis, Charles A.
Abstract : Core Ideas: Cover crop (CC) biomass production across temperate regions averaged 3.37 ± 2.96 Mg ha −1 . Ten high‐biomass producing CCs in temperate ecoregions were in this order: sorghum > sunn hemp > millet > rye > mixes > crimson clover > barley = hairy vetch > annual ryegrass > oat. Cover crop biomass production was greater in humid than semiarid regions and in areas with relatively high mean temperatures. Cover crop biomass production by cropping system was in this order: vegetables > other systems > maize > small grains. Cover crop biomass production generally increased with drill‐planting and increased seeding rate and growing season. Cover crop (CC) biomass production dictates agricultural and environmental services that CCs deliver, but finding a review on this topic is difficult. We synthesized published data on CC biomass production for 20 common CC species in temperate regions and discussed factors affecting CC biomass production. Review of 389 papers indicated CC biomass production was 3.37 ± 2.96 Mg ha −1 (mean ± SD). Cover crop biomass production for the top five biomass‐producing species was: sorghum ( Sorghum sp.) (5.99 Mg ha −1 ) > sunn hemp ( Crotalaria juncea L.) (5.77 Mg ha −1 ) > millet ( Pennisetum glaucum L.) (4.95 Mg ha −1 ) > rye ( Secale cereale L.) (4.93 Mg ha −1 ) > two‐species mix (4.18 Mg ha −1 ). In humid regions (>750 mm precipitation), CC biomass production ranged from 1.67 to 6.30 Mg ha −1 depending on species. In regions with <750 mm precipitation, CC biomass production ranged from 0.87 to 6.03 Mg ha −1 . Cover crop biomass production was in this order by cropping system: vegetables > other systems [soybean ( Glycine max L.), cotton ( Gossypium hirsutum L.), and others] > maize ( Zea mays L.) > small grains. Rye was among the most common and highest biomass producing species in most regions and cropping systems. Drill‐planting and maximizing CC growing season, such as early planting or late termination, can increase CC biomass production. Irrigation at establishment increased CC biomass production for legumes and mixes in humid regions, and all CC groups in semiarid regions. Overall, CCs can produce significant amount of biomass, but this can be highly dependent on climate, CC species, cropping system, and management.